Impact of natural mutations on the riboflavin transporter 2 and their relevance to human riboflavin transporter deficiency 2. Issue 7 (24th August 2021) - Console, Lara; Tolomeo, Maria; Cosco, Jessica; Massey, Keith; Barile, Maria; Indiveri, Cesare
Abstract: Riboflavin transporter deficiency 2 (RTD2) is a rare neurological disorder caused by mutations in the Solute carrier family 52 member 2 (Slc52a2) gene encoding human riboflavin transporter 2 (RFVT2). This transporter is ubiquitously expressed and mediates tissue distribution of riboflavin, a water‐soluble vitamin that, after conversion into FMN and FAD, plays pivotal roles in carbohydrate, protein, and lipid metabolism. The 3D structure of RFVT2 has been constructed by homology modeling using three different templates that are equilibrative nucleoside transporter 1 (ENT1), Fucose: proton symporter, and glucose transporter type 5 (GLUT5). The structure has been validated by several approaches. All known point mutations of RFVT2, associated with RTD2, have been localized in the protein 3D model. Six of these mutations have been introduced in the recombinant protein for functional characterization. The mutants W31S, S52F, S128L, L312P, C325G, and M423V have been expressed in E. coli, purified, and reconstituted into proteoliposomes for transport assay. All the mutants showed impairment of function. The K m for riboflavin of the mutants increased from about 3 to 9 times with respect to that of WT, whereas V max was only marginally affected. This agrees with the improved outcome of most RTD2 patients after administration of high doses of riboflavin.